Consumer Decision-Making Study Regarding the SUV Market in the Indian Context - Joghee, Shanmugan; Kabiraj, Sajal; Ramakrishnan, Swamynathan; Alzoubi, Haitham M. (Indian Journal of Marketing, 2024)
Purpose : The automobile industry relied significantly on the interplay between investors, manufacturers, and consumers. Understanding buyersâ€™ behavioral intentions, especially regarding sports utility vehicles (SUVs), is crucial for effective strategic planning and market success. This study analyzed the determinants of buyersâ€™ behavioral intentions toward SUV cars in the Indian market. Methodology : A quantitative approach was used to gather data from 1,048 respondents across 10 major Indian cities between October and December 2023. The data was analyzed using the partial least square-structural equation modeling (PLS-SEM) method. Findings : The factors â€œattitudeâ€ and â€œperceived conductâ€ showed a significant positive impact, while â€œsubjective normsâ€ had a relatively low impact. The strongest association was discovered between â€œperceived behavioral controlâ€ and â€œbehavioral intentionâ€ (0.776), followed by â€œattitudeâ€ (0.715) and â€œsubjective normsâ€ (0.512). Cronbachâ€™s alpha and composite reliability confirmed the replies (>0.7), while average variation extraction (>0.5) demonstrated convergent validity. Conclusion : The findings confirmed the significant role of the chosen determinants in shaping consumer behavioral intentions toward purchasing SUV cars. This insight would be crucial for stakeholders in the automobile industry to modify their strategies effectively. Limitations : The limited sample size may not represent the entire population, and emerging trends like electric vehicles or hybrid SUVs are not considered. Future research could focus on a larger sample size and the impact of cultural and economic diversity within India. Originality : Unlike earlier studies, this study used data from an emerging country to evaluate the determinants impacting behavioral intention among SUV buyers in the Indian market.